Contribution to the structure study of actual situation of plant mangrove communites in Xuan Thuy national park, Nam Dinh province - Thanh Huong, Phan Thi; Thai, Tran Huy; Cuong, Nguyen The; Phuong Anh, Tran Thi; Nam, Nguyen Hoai (Academia Journal of Biology, 2015)
This paper presented the result of the structural study of the actual plant mangrove forest communites in Xuan Thuy National Park. For the first time, the structure of six plant mangrove communities was analysized, the density of trees, generating stautus and rate were calculated by using standard plot and positioning plot methods. The biomass of the plant mangrove communities in Xuan Thuy national park were tested and calculated based on data from the diameter at breast height method. Results show that community which dominantes by A. corniculata (L.) Blanco, K. candel (L.) Druce, S. caseolaris (L.) Engl. has highest average biomass (about 216.6821 tons/ha), while community dominated by K. candel (L.) Druce, Sonneratia caseolaris (L.) Engl., Aegiceras corniculata (L.) Blanco), Rhizophora stylosa Griff. has lowest average biomass (about 56.5631 tons/ha).